Enhancing adaptive capacity through climate-smart insurance: Theory and evidence from India - Kramer, Berber; Ceballos, Francisco (International Association of Agricultural Economists, 2018)
Bundling agricultural insurance with climate-smart technologies and practices (CSA) can help improve risk management for smallholder farmers. This paper analyzes how bundling affects demand for insurance and CSA. Calibrating index insurance parameters to CSA payoff profiles increases the demand for insurance, but only when basis risk is low, and these effects of reducing basis risk itself. This raises the question how to bundle insurance products that leverage new technologies to provide indemnity insurance coverage with minimal basis risk. We therefore study the effect of bundling indemnity insurance with CSA technologies. Specifically, in a field experiment in India, we test whether conditioning insurance payouts on not burning residues improves residue management as a CSA technology. We find that this is the case, suggesting that indemnity insurance can help promote CSA technology adoption, but we also discuss shortcomings of this bundling approach, and identify potential alternatives to combine indemnity insurance and CSA technologies into a complementary risk management bundle.